High Presence of NETotic Cells and Neutrophil Extracellular Traps in Vaginal Discharges of Women with Vaginitis: An Exploratory Study - Fabiola Zambrano; Angélica Melo; Rodrigo Rivera-Concha; Mabel Schulz; Pamela Uribe; Flery Fonseca-Salamanca; Ximena Ossa; Anja Taubert; Carlos Hermosilla; Raúl Sánchez (Cells, 2022)
Infectious vaginitis is a microbiological syndrome of great importance in public health that affects millions of women worldwide. However, no studies have explored the phenomenon of the production of the neutrophil extracellular traps (NETs) that are released into the female reproductive tract in these pathologies. This study aimed to determine the presence of NETosis in vaginal discharges of women with bacterial vaginosis, candidiasis, and trichomoniasis by characterizing NETs. Extracellular DNA with neutrophil elastase and citrullinated histones was identified to confirm the NET components (n = 10). The concentration, phenotypes of NETs, and number of NETotic cells were determined. The results showed an increase in NETotic cells in women with Candida albicans (CA) and Trichomonas vaginalis (TV) and an increase in NETs in TV-induced vaginitis. Samples of CA- and TV-infected women showed different NET phenotypes (diffNETs, sprNETs, and aggNETs); diffNETs were found in high concentrations in samples with CA and were increased in three types of NETs in TV infections. Samples with intermediate microbiota and bacterial vaginosis showed increased NETotic cells while the intermediate microbiota presented a higher concentration of NETs. Therefore, alterations in the microbiota and the presence of fungal and parasitic infections are important stimuli for the activation and induction of NETosis, and their cytotoxic effects could enhance tissue damage.